Pengaruh Pembelajaran Berbasis Proyek Terhadap Hasil Belajar Logika Algoritma di IAIN Bukittinggi - Mathulhusna, Lina; Efriyanti, Liza; Supriadi, Supriadi; Okra, Riri (Indonesian Research Journal on Education, 2022)
This research is based on the results of the researchers' initial research in the Logic and Algorithm course in Informatics and Computer Engineering Education Study Program where the researchers found the following problems using conventional learning models such as Jigsaw Learning, Small Discussion and Student ActiveLearning which caused not all students to be able to understand Learning Logic and Algorithm. In addition, there were also problems from the lecturers who support Logic and Algorithm courses which stated that there was a lack of facilities in teaching and learning activities, especially in online learning situations, while inthis course they were required to form students' mindsets related to learning Logic and Algorithms. The type of research used by the author is quantitative research with the Quasi Experiment method. The research design used was the Pretest-Posttest Control Group Design. The sample of this research is PTIK students insemester 1 of class A class of 2021. The data collection technique is by using tests in the form of Pretest and Posttest. The data analysis technique used is the analysis prerequisite test which consists of normality test and homogeneity test as well as hypothesis testing. Based on the results of the research that has been carriedout, it is found that there is an effect of project-based learning models on student learning outcomes in the Logic and Algorithm course at the Informatics and Computer Engineering Education Study Program (PTIK) IAIN Bukittinggi, it can be seen from the results of the posttest of both classes. From the test results, it can be seen that the average difference in student learning outcomes in the experimental class and the control class is illustrated. By applying the project-based learning model, the students in the experimental class got a higher average score than the students who did not use the project-based learning model in the control class.